Patient satisfaction with healthcare services among health insurance program beneficiaries in Nepal: A cross-sectional study - Biraj Man Karmacharya; Sabina Marasini; Ruby Maka Shrestha; Sudim Sharma; Mukesh Adhikari; Samip Pandey; Sambhu Prasad Jnawali; Deepa Guragain; Ishwori Byanju Shrestha; Anjali Joshi; Bihari Sharan Kuikel; Nripa Raj Dangaura; et al. (PLoS ONE, 2025)
Background Patient satisfaction, often assessed through clients’ experiences and opinions are vital for improving healthcare services, shaping health policies, and providing feedback on the quality, availability, and responsiveness of healthcare services. In this study, we assessed the healthcare satisfaction levels of insured patients with the health services provided under the National Health Insurance Program (NHIP) accredited health facilities. Methods We conducted a cross sectional study at 22 health facilities across 3 provinces of Nepal. We utilized client-exit interviews among 468 patients enrolled and utilizing the health services under NHIP. We used a validated Patient Satisfaction Questionnaire III (PSQ-III) developed by RAND Corporation including various contextual socio- demographic characteristics. We calculated mean score and percentages of satisfaction across seven dimensions of patient satisfaction. To determine the association between various dimensions of patient satisfaction and socio- demographic characteristics of the patients, we used generalized ordered logistic regressions. Results Among 468 patients, we observed a wide variation in patient satisfaction across seven dimensions. About 87% of the patients were satisfied in the domain of interpersonal manner, 83% in technical quality, 63% in accessibility and convenience and 60% in financial aspects. The overall satisfaction was observed as 74%. The patients having chronic diseases among the family members were more satisfied compared to those having no chronic disease in the family members (AOR:5.96; 95% CI: 2.65–13.39). Presence of chronic disease and subsidy status were found to be associated with patient satisfaction in most dimensions. Conclusions Patient satisfaction measures the gap between expected and actual service experience, tied to service quality, availability, accessibility, and financial aspects. While NHIP aims to provide quality services, the actual service quality mainly depends on the efforts of the health facilities. Therefore, strengthening the health system is crucial for improving service quality and ensuring user retention and satisfaction with NHIP.